Characteristics of COVID-19 cases and factors associated with their mortality in Katsina State, Nigeria, April-July 2020 - Suleiman Idris Ahmad; Kabir Suleiman; Bello Umar Ibrahim; Shamsuddeen Suleiman Yahaya; Kabir Mustapha; Ibrahim Muhammad Kaita; Suleiman Ahmed Haladu; Bello Suleiman Abdullahi; Augustine Olajide Dada; Suleiman S Bashi; Adamu D Dawud; Ahmed Tijani Abubakar; et al. (Journal of Interventional Epidemiology and Public Health)
Introduction: COVID-19 was first detected in Daura, Katsina State, Nigeria on 4 April 2020. We characterized the cases and outlined factors associated with mortality.